SARS-CoV-2 affected cells Pathogeny and Therapy - M.R Ponizovskiy (International Journal of Coronaviruses, 2020)
There were compared mechanisms infecting a human organism by different viruses in relation to interaction between human diploid cellular cycle mechanisms and coronaviruses haploid genomic mechanism. Besides there were described mechamism forming combined haploid-diploid cellular cycle of viral affected cells due to interactions between human cellular cycle mechanisms and coronaviruses genomic mechanism. Further there were considered infected way of SARS-CoV-2 from mechanism maintenance stability Internal Energy of an organism’s able-bodies cells and transmutation them into viral affected cells leading to death of affected cells of high respiratory level in nose-trachea-bronchi with transiting coronaviruses through dead cells‘ wall and infecting lungs‘ cells. Taking into account great searches of methods treatments Coronaviruses infected disease, we offered to approved through detail clinical Trial of new efficient method of treatment ill patients with SARS-CoV-2 disease which can rescue of still alive lungs‘ cells. Moreover there was reviewed offered therapy of SARS-CoV-2 induced disease.
Keywords: Coronaviruses